Enhancing the production of phycocyanin biopigment from microalga Arthrospira maxima through medium manipulation utilizing Box-Behnken Design - MUHAMMAD SYAWALUDDIN HILMI YAHYA; MURNI HALIM; FADZLIE WONG FAIZAL WONG; HELMI WASOH; JOO SHUN TAN; MOHD SHAMZI MOHAMED (Nusantara Bioscience, 2024)
Abstract. Yahya MSH, Halim M, Wong FWF, Wasoh H, Tan JS, Mohamed MS. 2024. Enhancing the production of phycocyanin biopigment from microalga Arthrospira maxima through medium manipulation utilizing Box Behnken Design. Nusantara Bioscience 16: 263-276. Phycocyanin is among the valuable pigments produced by microalgae Arthrospira spp. possessing significant nutritional and coloring properties. It is widely used in food, nutraceutical, and biotechnology applications. Presently, Arthrospira platensis is a species very much established for producing phycocyanin commercially. Given the extensive research works and understanding of A. platensis, there exists a significant opportunity to explore lesser-studied but potentially valuable strains, such as A. maxima, specifically for pigment production capabilities. This study aims to optimize the phycocyanin production from the A. maxima by first considering vital media components for phycocyanin secretion by the microalgal cells, namely sodium nitrate, sodium bicarbonate, dipotassium phosphate, sodium chloride and a number of precursors. Upon identifying the most significant factors, their composition in the NRC production medium was manipulated using Response Surface Methodology (RSM). Initial screening using the Plackett-Burman Design revealed two macronutrients and a precursor that significantly affected the target response (?>0.05): sodium nitrate, dipotassium phosphate and glutamic acid. The three factors were further refined using the Box-Behnken Design (BBD), a variation of the RSM technique. In one BBD run, the highest phycocyanin yield was 224.86 mg/L, achieved using a recipe comprising 0.0125 M sodium nitrate, 0.375 mM dipotassium phosphate and 0.625 mM L-glutamic acid. This resulted in an increase of 37.85% improvement over the basal medium. BBD's validating recipe comprising 0.0125 M sodium nitrate, 0.375 mM dipotassium phosphate and 0.625 mM L-glutamic acid then produced 235.98 g/L of phycocyanin, which in turn has a 44.67% improvement of phycocyanin yield compared with an unoptimized NRC medium. This significant increase in phycocyanin yield demonstrates the potential of this research to enhance phycocyanin production for commercial use and further research. In conclusion, optimizing the composition of a medium can significantly increase phycocyanin production.